Eiger and its receptor, Wengen, comprise a TNF-like system in Drosophila. - Kauppila, S.; Maaty, W.S.; Chen, P.; Tomar, R.S.; Eby, M.T.; Chapo, J.; Chew, S.; Rathore, N.; Zachariah, S.; Sinha, S.K.; Abrams, J.M.; Chaudhary, P.M. (Oncogene, 2003)
In mammals, members of the tumor necrosis factor (TNF) family play an important role in the regulation of cellular proliferation, differentiation and programmed cell death. We describe isolation and characterization of an orthologous ligand/receptor axis in Drosophila. The ligand, designated Eiger, is a type II membrane glycosylated protein, which can be cleaved at residue 145 and released from the cell surface as a soluble factor, thereby representing the first potential cytokine to be described in Drosophila. Eiger exists in two alternatively spliced isoforms, Eiger long (Eiger-L) and Eiger short (Eiger-s), both of which are expressed throughout development and in the adult. We also describe the isolation and characterization of a novel Drosophila member of the TNF receptor family, designated Wengen, which is a type I membrane protein that can physically interact with the recently described TRAF2 homolog dTRAF2. Both Eiger and Wengen are expressed in distinctive patterns during embryogenesis and Eiger is responsive to genotoxic stress. Forced expression of Eiger-L, Eiger-s or Wengen, caused apoptotic cell death which could be rescued by caspase inhibitors or the JNK phosphatase Puckered. In addition, Eiger-induced cell killing was attenuated by RNAi-mediated suppression of Wengen. Our results illustrate that Eiger and Wengen represent proximal components of an evolutionarily conserved TNF-like signaling pathway in Drosophila.